Sport and politics in a complex age. Issue 5 (4th May 2018) - Hassan, David
Abstract: This article examines the complex nature of the relationship between international sport and politics in the twenty-first century. It does so by considering the cultural and geo-political profiles of those countries that are expressly pursuing the hosting of major international sporting events, such as the Olympic Games and the FIFA World Cup. It focuses, on the emergence of a raft of 'new' countries seeking to stage such global mega-events and considers why they would be so keen to do so when, based on participation levels amongst their indigenous peoples such a decision would appear to have little popular support. More to the point, there would seem to be increasing commonality amongst these 'new' nation-states in terms of their political profiles, their attitudes towards minorities, their approach to the advancement of a rights agenda, and to their motivations for hosting major sporting events in the first instance. Ultimately the article poses the question of whether sport should readily lend its remaining credibility to such nation-states or whether its ready acquiescence of the same actually says more about its virtual preoccupation with commercial return, persistent mal-governance or, in some cases, corruption.